An open trial of brief transdiagnostic internet treatment for anxiety and depression - Dear, B.; Titov, N.; Schwencke, G.; Andrews, G.; Johnston, L.; Craske, M.; McEvoy, Peter (Elsevier, 2011)
The present study evaluated the efficacy of a brief version of an internet-administered transdiagnosticCBT protocol, the Wellbeing Program (Titov et al., 2011), designed to treat three anxiety disorders andmajor depression within the same program. This brief version included the same core CBT skills as theoriginal, but condensed the materials from 8 to 5 online lessons, reduced the duration of treatment from10 to 8 weeks and did not include an online forum. Thirty-two individuals with a principal diagnosis ofmajor depression, generalised anxiety disorder, panic disorder or social phobia received CBT-basedonline educational lessons, homework assignments, weekly contact from a clinical psychologist andautomated emails. Eighty-one percent of participants completed the lessons within the 8 week program.Post-treatment and 3-month follow-up data were collected from 28/32 and 31/32 participants respectively. Participants improved significantly on the Depression Anxiety and Stress Scales e 21 Item, Patient Health Questionnaire e 9 Item, and Generalised Anxiety Disorder e 7 Item scales, with corresponding within-group effect sizes (Cohen’s d) at follow-up of 1.05, .73, and .95, respectively. Participants rated the procedure as highly acceptable with gains of a similar magnitude as those found for the original program, but less time was spent per participant by the clinician in the present trial (mean ¼ 44.61 min, SD ¼ 34.45) compared to the original program (mean ¼ 84.76 min, SD¼ 50.37). These results provide additional support for the efficacy of transdiagnostic iCBT in the treatment of anxiety and depressive disorders and indicate that a brief version may be of benefit.